The Influence of Leverage, Liquidity, and Profitability on Sukuk Ratings of Companies Listed at PT PEFINDO - Yuhana, Winda; Kartini, Kartini (MEC-J (Management and Economics Journal), 2025)
This study examines the impact of leverage, liquidity, and profitability on sukuk ratings for companies listed on PT Pefindo during 2020– 2023. Using a quantitative approach and secondary data from financial reports, 12 companies with 48 observations were analyzed through purposive sampling and EViews 12. The findings reveal that leverage does not significantly affect sukuk ratings, indicating that corporate debt levels are not the primary focus in sukuk evaluations. Liquidity has a significant positive effect, showing that higher liquidity enhances sukuk ratings. Profitability also shows no significant impact, suggesting that profit levels are not a key consideration in sukuk assessments. These results highlight the importance of liquidity management for issuers in improving sukuk appeal and provide insights for investors in evaluating sukuk risks and returns. This study contributes to Islamic finance literature by identifying factors influencing sukuk ratings.